Building Climate Resilient Agriculture in Caribbean Countries: Trinidad and Tobago - Hayman, Alicia A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Trinidad and Tobago's agriculture sector contributes only 1.2% to the country's GDP, but it employs over 4% of the population and plays a crucial role in diversifying the economy. However, the sector faces challenges in including mitigation measures due to limited data availability, low monitoring, reporting, and verification capacity, and policies that do not address climate change. Additionally, low awareness of Nationally Determined Contribution goals and purposes among farmers, extension officers, and government workers affects data collection and implementation of mitigation or adaptation actions. To enhance the country's climate ambition, T&T can focus on reducing emissions from fertilizer use, enteric fermentation, and manure management in crop and livestock production. Improved emission data for rice cultivation could also help identify feasible emission reduction options for this category.